Perancangan Media Pemasaran UMKM Toko Sembako P.E Menggunakan Website OpenChart - Hafiz, Muhammad; Ardiansyah, Alfin (Yayasan Lembaga Studi Makwa, 2023)
This study examines the strategy for developing digital-based promotional media to support the growth of micro, small, and medium enterprises (MSMEs), with a case study on Toko Sembako P.E. located in Bukittinggi. This MSME operates in the sale of daily necessities such as rice, cooking oil, and instant noodles. Facing market competition and the limitations of conventional promotion methods, this research aims to design a digital solution to enhance competitiveness and expand market reach. The main focus of this study is the utilization of social media and the development of an e-commerce platform as tools for promotion and transactions. The research method employs a descriptive approach through system design stages, including needs analysis, user interface (UI) design, and website development using OpenCart as the e-commerce platform. The result of this research is an online store website integrated with social media, allowing customers to access product information more widely and conduct transactions efficiently. The website is designed to be user-friendly, responsive, and equipped with essential features such as product catalogs, shopping carts, payment systems, and order tracking. With this digital promotional media, Toko Sembako P.E. is expected to enhance its online visibility, reach new customers, and optimize product sales. This study demonstrates that the digitalization of promotion and sales can be an effective strategy for MSMEs in facing the digital transformation era, while also contributing to sustainable local economic growth.